Letter (copy) - Citrine, Walter, 1887-1983
012b-0008-001 International WMC/AC/467 18th [20th] September, 1939 The Rt. Hon. Viscount Halifax, K.G., G.C.S.I., G.C.I.E., Foreign Office, Downing Street, WHITEHALL. S.W.1. Dear Lord Halifax, I thank you for your letter of 15th September, with regard to our request to you to intercede on behalf of Jose Rodriguez Vega. I fully appreciate the difficulties which must be involved in any intervention by Sir Maurice Peterson in this case, and I am grateful to you for your assurance that he will do all he can to help. Yours sincerely, General Secretary. 292/946/12b/8